PROGRAM SMK (SAYA MURID KRISTUS) SEBAGAI PENDEKATAN YANG MENGUATKAN PANGGILAN DALAM AMANAT AGUNG DI GBI BETHEL BANDUNG - Yahya Fajar Edhi Nugroho; Yanto Paulus Hermanto; Rubin Adi Abraham (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
Abstract In the realization of the implementation of the Great Commission of Christ, the church, apart from preaching or evangelizing, the church also performs discipleship or is often referred to as teaching new souls and their congregations. A church that has experienced the benefits of the discipleship process will surely grow in the spiritual quality of its congregation. The effect of the benefits that can be seen is that someone who has followed the process of discipleship, that person will certainly grow his spiritual life towards spiritual maturity. Spiritual maturity is very important for believers so that their lives truly reflect the character of Christ. Christians who have reached the spiritual maturity stage will have a strong and solid faith amidst the onslaught of the influence of misleading teachings (false gospels) and amidst the challenges of the storms of life during the Covid-19 pandemic and have a heart's desire to serve God with love faithful so that many new souls are brought to Christ. Through this paper, the author will invite readers to find out what effective steps for discipleship will be during the Covid-19 pandemic?